Impact of biodiesel demand on the Malaysian palm oil export: A simultaneous equations approach - Applanaidu, Shri Dewi; Mohd Arshad, Fatimah; Shamsudin, Mad Nasir; Yusop, Zulkornain; Alias, Mohammad (2011)
In the last few years, against the background of increasing concerns regarding the energy supply security as well as environmental concern, there has been an increase in interest on renewable energy sources. This has resulted in some countries looking for bio-based alternative energies which lead to the increase in demand for bio-based feedstocks such as palm and rapeseed oil (for bio-diesel) and sugar cane and corn (for ethanol). The European Union (EU) Renewable Energy Directive requires reduction of green house gases (GHG) emissions by at least 35 percent compared with fossil fuels, so that biodiesel is classfied as "sustainable" and help to spur growth of green technologies. One of the new elements in the palm oil market is the growing demand for this commodity as a feedstock to biodiesel production. This will also put Malaysia in a better light on the international front for taking the effort to reduce carbon emissions. In line with this, the palm oil sector in Malaysia will be able to match the New Economic Model's (NEM) major goals of high income, sustainability and inclusiveness. This new development is affecting the dynamics of the market, in particular, the supply and demand sectors of this commodity. This paper seeks to examine the impact of biodiesel demand on the Malaysian palm oil export. This paper proposes a structural econometric model consisting of nine structural equations and four identities. The model has been estimated by two stage least squares method using annual data for the period 1976-2010. The specification of the structural model is based on a series of assumptions about general economic conditions, agricultural policies and technological change.